PENERAPAN FUZZY TOPSIS UNTUK SELEKSI PENERIMA BANTUAN KEMISKINAN - Ni Kadek Sukerti (Jurnal Informatika, 2015)
Some factors that cause mis target of poor relief are inacurate criteria of poor citizen as well as inexactly method that make error in manual calculation. Fuzzy Technique for Order Preference by Similarity to Ideal Solution Method (Fuzzy TOPSIS) is used to select the receiver of poor relief in order to make alternative ranking to compare. It’s implementation is by using excel and matlab with ten alternative (village) which is will compare based on their criteria and subcriteria. The criteria that will be use is the look of their house, family (card) member, ownership of house land, and their work for living, monthly revenue, and level of education. The output of this method is total preference point of all criteria. The highest point will be priority to have poor relief. Its validation will be done by comparing the result of Fuzzy TOPSIS through Ms. Excel and Matlab and have the same results. The last decision will be at the stakeholder and this Fozzy TOPSIS results can be used to decision making acceleration. The data that used can be from related official and by library investigation.Key word: Information System, Fuzzy TOPSIS, Poor Relief, Ranking.